New Norm in Consumer Buying Pattern: Online Shopping Swing amid the Coronavirus Pandemic - Sinha, Rupesh; Nair, Rajesh Kumar; Naik, Veena; Ganatra, Varsha; Singri, Prarthana; Singh, Padmalini; Kamble, Ashwin Ravindra; Kaakandikar, Rishikaysh; KJ, Sirisha; Modawal, Ishaan (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2021)
A drastic shift in the market environment was observed with the pandemic situation spread all around the world. The number of people at the workplace or marketplace also shrunk from thousands to hundreds, tens, and one-digit numbers with the thought of avoiding the crowd and being in isolation or separations to avoid contact. This rapid change in situation has brought huge overnight changes in the shopping behaviors of the customers from bulk buying in a physical market or family shopping to online shopping of all fast-moving consumer goods. There are beginnings of a shift in this approach in India. The study emphasizes the factors influencing online shopping, benefits, and challenges faced by the customers, and the preferred mode of buying for listed products along with the mode of payment. Suggestive measures to bring positive change are also discussed in the paper.